2018
DOI: 10.1089/mdr.2017.0073
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial, Multidrug-ResistantKlebsiella pneumoniaeStrains Isolated from Mexico City Produce Robust Biofilms on Abiotic Surfaces but Not on Human Lung Cells

Abstract: Kpn strains isolated from nosocomial infections in Mexico City are MDR, although the majority are still susceptible to carbapenems and form more robust biofilms on polystyrene in comparison to those formed on human cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Other studies showed similar or slightly higher proportion of Enterobacter strains that can form biofilms 28,29 . The high rate of biofilm-producing K. pneumoniae and the variability among E. coli isolates found in this study are in concordance with other studies evaluating MDR strains 14,30,31 .…”
Section: Discussionsupporting
confidence: 93%
“…Other studies showed similar or slightly higher proportion of Enterobacter strains that can form biofilms 28,29 . The high rate of biofilm-producing K. pneumoniae and the variability among E. coli isolates found in this study are in concordance with other studies evaluating MDR strains 14,30,31 .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, several studies report the association of antibiotic resistance with biofilm formation in clinical isolates of Klebsiella spp. [11][12][13][14]. Moreover, the role of fimbriae in adhesion and biofilm formation by Klebsiella is also well documented [15,16].…”
Section: Introductionmentioning
confidence: 96%
“…Antibiotic resistance was determined in clinical isolated strains using Vitek2 ® , so classification according to criteria described in this work, could be applied, obtaining a higher MDR strains percentage (16) reported that 80% of a Mexico City hospital isolated strains were MDR, nevertheless, no PDR strain was obtained, whereas in this study, one PDR strain was found. This allows us to visualize the increasing resistance of K. pneumoniae due to indiscriminate use of antibiotics for treatment of infection caused by this bacterium.…”
Section: Discussionmentioning
confidence: 84%